Examining the exposure, timing, and frequency of interpersonal communication contacts to improve infant and young child feeding in Bangladesh, Ethiopia, and Vietnam (P10-138-19) - Kim, Sunny S.; Nguyen, Phuong Hong; Tran, Lan Mai; Alayon, Silvia; Menon, Purnima; Frongillo, Edward A. (Oxford University Press, 2019)
In the context of large-scale interventions to improve infant and young child feeding (IYCF) practices, we examined differences in characteristics of those exposed and not exposed to interventions; exposure to interpersonal communication (IPC), including overlap with other interventions and timing and number of contacts; and relationship between frequency of IPC contacts and IYCF practices.